Proteinuria in a patient with the diaphragmatic hernia-hypertelorism-myopia-deafness syndrome: further evidence that the facio-oculo-acoustico-renal syndrome represents the same entity. Issue 1 (January 1998) - Devriendt, K; Standaert, L; Van Hole, C; Devlieger, H; Fryns, J P
Abstract : We present a male infant with hypertelorism, severe myopia and sensorineural deafness, diaphragmatic hernia, and proteinuria. This patient combines features of two distinct genetic conditions, the syndrome of diaphragmatic hernia, exomphalos, absent corpus callosum, hypertelorism, myopia, and sensorineural deafness (MIM 222448), and the facio-oculo-acoustico-renal syndrome (MIM 227290), which is characterised by similar anomalies, with the additional finding of proteinuria, but without diaphragmatic hernia. The present observations further suggest that these syndromes are the variable expression of a single autosomal recessive disorder.